2010
DOI: 10.1038/emboj.2010.256
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of MIP-1 chemokine (CCL3 and CCL4) and clearance of MIP-1 by insulin-degrading enzyme

Abstract: Macrophage inflammatory protein-1 (MIP-1), MIP-1α (CCL3) and MIP-1β (CCL4) are chemokines crucial for immune responses towards infection and inflammation. Both MIP-1α and MIP-1β form high-molecular-weight aggregates. Our crystal structures reveal that MIP-1 aggregation is a polymerization process and human MIP-1α and MIP-1β form rod-shaped, double-helical polymers. Biophysical analyses and mathematical modelling show that MIP-1 reversibly forms a polydisperse distribution of rod-shaped polymers in solution. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
175
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(187 citation statements)
references
References 58 publications
10
175
2
Order By: Relevance
“…In fact, we found that MIP-1a could not reproduce the effect of ECI301 in the combination treatment with radiation (unpublished observation). It has been reported that the basic unit of one MIP-1a molecule is a dimer, whose primary contact is constituted by two antiparallel b strands formed by an N-terminal loop (38,39). In MIP-1a molecules, the hydrogen bonds between Asp27 and Arg46/ Arg48 residues, and between Asp6 and Ser33, and the hydrophobic interaction between Tyr28 and Phe24 residues are proposed to contribute to the interaction between the two dimers, and subsequent polymer formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we found that MIP-1a could not reproduce the effect of ECI301 in the combination treatment with radiation (unpublished observation). It has been reported that the basic unit of one MIP-1a molecule is a dimer, whose primary contact is constituted by two antiparallel b strands formed by an N-terminal loop (38,39). In MIP-1a molecules, the hydrogen bonds between Asp27 and Arg46/ Arg48 residues, and between Asp6 and Ser33, and the hydrophobic interaction between Tyr28 and Phe24 residues are proposed to contribute to the interaction between the two dimers, and subsequent polymer formation.…”
Section: Discussionmentioning
confidence: 99%
“…In MIP-1a molecules, the hydrogen bonds between Asp27 and Arg46/ Arg48 residues, and between Asp6 and Ser33, and the hydrophobic interaction between Tyr28 and Phe24 residues are proposed to contribute to the interaction between the two dimers, and subsequent polymer formation. In ECI301, whose basic unit is also a dimer, Asp27 of MIP-1a is substituted with Ala. MIP-1a forms a double-helical polymer burring its receptor-binding sites, whereas substitution of Asp27 with Ala results in irregular polymers with possible dissociation (39). The ECI301 molecule used in the present investigation was found to be a mixture of tetramer (76%), dimer (20%), and polymers larger than tetramer (the remainder) at mg/mL concentration and no significant difference of this ratio was found at 10 mg/mL (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…In the macaque model of CHIKV infection, an up-regulation of IFN-/, IFN-, MCPs, IL-6 and TNF- was detected, all synonymous with a strong, macrophage-induced inflammatory response (Labadie et al, 2010). IL-1, RNI and TNF- are factors known to trigger apoptosis (Bhaumik & Khar, 1998;Griffin & Hardwick, 1997;Roulston et al, 1999) while MCP-1 and MIP-1 are involved in amplifying the inflammatory response (Carr et al, 1994;Lidbury et al, 2008;Ren et al, 2010;Wolpe et al, 1988). Macrophages have also been implicated as a cellular reservoir for alphavirus persistence and therefore a contributing factor in the development of chronic disease symptoms.…”
Section: Cellular Factors In Alphavirus Induced Myopathiesmentioning
confidence: 99%
“…Our finding of the hyperactive mutation at the hinge loop also suggests a new way to boost IDE catalysis. Because IDE is a key protease in the destruction of amyloidogenic peptides (12) and novel biologically relevant substrates of IDE, such as MIP-1α and calcitonin generelated peptide, continue to be discovered (11,32), future studies will address how conformational dynamics are linked to the catalytic cycle of IDE and how to control such processes. Such information can also provide avenues to design IDE-based therapies for modulating proteostasis in humans.…”
Section: Roles Of Ide Swinging Door In Substrate Recognition and Rate Ofmentioning
confidence: 99%
“…S1) (3, 7). IDE uses the size, shape, and charge distribution of its chamber (∼13,000 Å 3 ) to selectively engulf structurally diverse peptides, such as insulin, Aβ, tumor growth factor-α, macrophage inflammatory protein-1α (MIP-1α), natriuretic peptides, and amylin (7)(8)(9)(10)(11). IDE substrates are presumably unraveled inside the catalytic chamber and then stochastically cleaved in regions that have a high propensity to convert into a β-strand for the formation of intermolecular cross-β sheets, the fundamental structural element of amyloid fibrils (7)(8)(9).…”
mentioning
confidence: 99%